IMPLEMENTASI KEBIJAKAN PENATAAN ORGANISASI DALAM RANGKA PENINGKATAN EFEKTIVITAS PENYELENGGARAAN PEMERINTAHAN DI KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA - Hatidjah, Christo (JURNAL ADMINISTRASI PUBLIK, 2014)
ABSTRACT: Policy implementation of structuring organization subdistrict government as defined in PP. Numb. 41 years 2007 about equipment organization of the region and PP. Numb, 19 years 2008 about subdistrict, be expected can realize effectiveness of subdistrict governance. But the reality showed that subdistrict governance notoptimallyeffective. In connection with that problem then this research intending to know how to policy implementation of structuring organization government of Subdistrict Pasan, and to know what if that policy implementation has been to able increased effetiveness of subdistrict governance. This research using qualitative method. Data sources/informant taked from elements government apparatus of subdistrict and the peoples Subdistrict Pasan, totally 15 people. Data collection used interview technic. Whereas data analyze used analyze qualitative the interactive model from Miles and Hubernan. Research results showed : (1) organization government Subdistrict Pasan already laid out according with the resolve PP.41/2007 and PP.19/2008, but largely the structural position (section head) unfilled from definitive official because deficiency ofqualifiedstaffedforthe job. (2) effectiveness of subdistrict governance not optimally views from level ability and successly carry out program/activities implement of task general governance and implementation of regional autonomy becomes the scope of government’s duty subdistrict. Based on that research results get a conclusion the policy implementation of structuring organization of subdistrict government has been expect or increased effectiveness of subdistrict governance, but not optimally. Based on conclusion research results recommended that positions structural (section head and sub section head) empty of government at Subdistrict Pasan immediatelyfilled by the staff meet of terms. Keywords : policy structuring organization, effectiveness subdistrict government